Maximum strength and power as determinants of match skating performance in elite youth ice hockey players - Keiner, M.; Kierot, M.; Stendahl, M.; Brauner, T.; Suchomel, T. J. (The Journal of Strength and Conditioning Research, 2024)
Maximum strength has a strong influence on speed-strength performances such as sprints and jumps. Important for sports practice is whether these findings are also reflected in game performance. Therefore, the aim of this study was to explore the influence of maximum strength and power performance on linear on-ice skating performance in testing and during game play. A cross-sectional study was conducted, and 24 highly trained male youth ice hockey players participated. Jump performances (countermovement jump [CMJ], drop jumps), maximum strength (1 repetition maximum [1RM] squat and isometric trap bar pull [ITBP]), and on-ice linear sprints (15 m [LS15], 30 m [LS30], flying 15 m [FLY15]) were measured. Match performances (among others: peak skating speed) were collected of 4 regular league games using a local positioning system. Correlation coefficient and explained variance were calculated (? = 0.05). Correlations between maximum strength and jump with on-ice linear sprint performance showed 1-35% explained variance. Correlations between "off ice" test (CMJ, relative 1RM) and game data (peak skating speed) showed 22-30% explained variance, respectively, while ITBP and DJ missed significant level. Between linear sprint and game performance showed 15-59% explained variance. In this study, a clear influence of 1RM in squatting and CMJ performance on on-ice linear sprint as well as in-game peak skating speed was observed. These findings show that strength and jumping performance can be valuable tests within a comprehensive test battery and indicate the relevance of strength and jumping tasks within the regular exercise program to improve in-game skating performance.